The road to evolution of ProTx2: how to be a subtype-specific inhibition of human Nav1.7 - Zhao, Fan; Liu, Yuanyuan; Liu, Yiyu; Ye, Qi; Yang, Hongtao; Gui, Mingze; Song, Yongbo (Frontiers in Pharmacology, 2024)
The human voltage-gated sodium channel Nav1.7 is a widely proven target for analgesic drugs studies. Protx2, a 30-residue polypeptide from Peruvian green tarantula venom, shows high specificity to activity against human Nav1.7, suggesting its potential to become a non-addictive analgesic. However, its high sensitivity to human Nav1.4 raises concerns about muscle side effects.Here, we engineered three mutants (R13A, R13D, and K27Y) of ProTx2 to evaluate their pharmacological activities towards Nav1.7 and Nav1.4. It is demonstrated that mutant R13D maintained the analgesic effect in mice while dramatically reducing its muscle toxicity compared with ProTx2. The main reason is the formation of a strong electrostatic interaction between R13D and the negatively charged amino acid residues in DII/S3-S4 of Nav1.7, which is absent in Nav1.4. This study advances our understanding and insights of peptide toxins, paving the way for safer, effective non-addictive analgesic development.